2016
DOI: 10.1016/j.bbi.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular administration of TNF-like weak inducer of apoptosis induces depression-like behavior and cognitive dysfunction in non-autoimmune mice

Abstract: Fn14, the sole known signaling receptor for the TNF family member TWEAK, is inducibly expressed in the central nervous system (CNS) in endothelial cells, astrocytes, microglia, and neurons. There is increasing recognition of the importance of the TWEAK/Fn14 pathway in autoimmune neurologic conditions, including experimental autoimmune encephalomyelitis and neuropsychiatric lupus. Previously, we had found that Fn14 knockout lupus-prone MRL/lpr mice display significantly attenuated neuropsychiatric manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…To evaluate the therapeutic effect of GW2580 administration on cognitive function, an object placement (spatial memory) test was conducted. Generally, animals possess an innate preference to explore objects in novel locations, and a preference score of more than 53% indicates preserved memory [26]. However, mice treated with GW2580 exhibited a preference score of 44.1% ± 6.4 %, suggesting that they are incapable of recalling the original placement of the object, similar to the control treated animals (52.3% ± 6.6%) (p=NS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate the therapeutic effect of GW2580 administration on cognitive function, an object placement (spatial memory) test was conducted. Generally, animals possess an innate preference to explore objects in novel locations, and a preference score of more than 53% indicates preserved memory [26]. However, mice treated with GW2580 exhibited a preference score of 44.1% ± 6.4 %, suggesting that they are incapable of recalling the original placement of the object, similar to the control treated animals (52.3% ± 6.6%) (p=NS).…”
Section: Resultsmentioning
confidence: 99%
“…Cytokine dysregulation has been proven to be directly associated with depression by numerous studies [33, 36]. Intracerebroventricular injection of microglia-derived cytokines such as TWEAK and IL-6 directly result in depression-like behavior in vivo [26, 37]. In addition, systemic inflammatory mediators may also induce negative behavior outcomes by accessing the brain via the BBB, or directly acting on the vagus nerve [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytokine TNF-like weak inducer of apoptosis (TWEAK) has been found to play a role in the pathogenesis of NPSLE (and other neuropathologies, such as stroke and EAE) [16, 6165]. Evaluation of human cerebral microvascular endothelium in culture found that TWEAK signaling induced increased expression of cytokines, including IL-6 and IL-8, as well as ICAM-1 and E-selectin [66].…”
Section: The Bbb Is One Of Three Brain Barriersmentioning
confidence: 99%
“…Autoantibody deposition leads to neurotoxicity and glial cell activation, which can in turn produce abundant, locally enriched cytokines in the CNS, ultimately resulting in behavioral abnormalities. Further, elevated cytokines within the CNS, such as TWEAK, are able to induce neuropsychiatric manifestations directly by mediating inflammatory responses of brain resident cells [8]. It should also be noted that some systemically elevated cytokines can alter behavior directly through the vagus nerve, without ever passing through the BBB [9].…”
Section: Introductionmentioning
confidence: 99%